International Courts and atrocities in the XXI century - Pérez León Acevedo, Juan Pablo (2022)
Mass atrocities perpetrated in the last years of the last century and those committed in the XXI century have received major attention from a wide arrange of actors. Indeed, these serious violations of human rights and international humanitarian law, which are constitutive of international crimes, have led to cases before supranational courts. The law and/or practice of international courts within their respective specific mandates demonstrate that there is an increasing international judicial engagement with rendering justice in scenarios of mass atrocities. In this context, the main research question addressed in this article is to identify some of the main contributions of international courts in mass atrocity cases in the XXI century. In this context, three supranational courts are taken into account: the International Court of Justice, the International Criminal Court, and the Inter-American Court of Human Rights.